LEAST COST HOMEMADE STARTER’S RATION EFFECT ON GROWTH PERFORMANCE OF INDIGENOUS AND SASSO BREED CHICKS - GULILAT, LEMMA; TEGEGNE, FIREW; DEMEKE, SOLOMON (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The objective of this study was commercial starters ration substitution by least-cost ration in various levels on the growth performance of Indigenous and Sasso chicks in Farta Woreda. The research area is 666km far from the capital city of Addis Ababa, Ethiopia. A total of 150 Indigenous local and 450 Sasso T-44 day-old chicks were randomly assigned into five dietary groups, which contained 0% (T5), 25 (T4), 50 (T3), 75 (T2), and 100 (T1) of commercial starter’s ration in factorial completely randomized design (CRD) with 3 replications for two months feeding period. The results showed that the commercial ration level decreased and the increased level of the least cost homemade ration was significantly low (p<0.001) retaining dry matter and nitrogen, mean daily feed consumption and metabolizable energy. On the opposing, there was an increase in fiber content and feed conversion ratio in high-level dilution of starter’s commercial diet with a homemade diet. Yet, chicks on 0, 25, and 50% commercial starters rations groups substituted by homemade rations were significantly higher (p<0.001) in daily weight gain, feed conversion ratio, mean daily feed intake and final body weight attained. According to these results, up to 50% of expensive commercial starter rations were replaced by the least-cost homemade ration without adversely affecting the growth performance of chicks.